Dissecting interplays between Vitis vinifera L. and grapevine virus B (GVB) under field conditions. (28th September 2018) - Chitarra, Walter; Cuozzo, Danila; Ferrandino, Alessandra; Secchi, Francesca; Palmano, Sabrina; Perrone, Irene; Boccacci, Paolo; Pagliarani, Chiara; Gribaudo, Ivana; Mannini, Franco; Gambino, Giorgio
Summary: Plant virus infections are often difficult to characterize as they result from a complex molecular and physiological interplay between a pathogen and its host. In this study, the impact of the phloem‐limited grapevine virus B (GVB) on the Vitis vinifera L. wine‐red cultivar Albarossa was analysed under field conditions. Trials were carried out over two growing seasons by combining agronomic, molecular, biochemical and ecophysiological approaches. The data showed that GVB did not induce macroscopic symptoms on 'Albarossa', but affected the ecophysiological performances of vines in terms of assimilation rates, particularly at the end of the season, without compromising yield and vigour. In GVB‐infected plants, the accumulation of soluble carbohydrates in the leaves and transcriptional changes in sugar‐ and photosynthetic‐related genes seemed to trigger defence responses similar to those observed in plants infected by phytoplasmas, although to a lesser extent. In addition, GVB activated berry secondary metabolism. In particular, total anthocyanins and their acetylated forms accumulated at higher levels in GVB‐infected than in GVB‐free berries, consistent with the expression profiles of the related biosynthetic genes. These results contribute to improve our understanding of the multifaceted grapevine–virus interaction.